Aspectos críticos na condução do pregão eletrônico : uma abordagem a partir da opinião de pregoeiros da UFES - Puton, Roseni (2017)
Procurement section plays a strategic role in achieving organizations objectives. In the public sphere, this role is even more important due to the origin of the resources involved and the meeting to the public interest. The search for improvements in this area becomes even more necessary. In this connection, the electronic auction emerged to bring more efficiency and transparency to public procurement. The present research deals with the critical issues regarding to the conduction of this tool within a federal autarchy from its auctioneers opinion. The aim of this study was to reveal the criers opinions about the use of the modality, to identify the major difficulties and obstacles during the conduct of the process and to know their positions and attitudes toward to the exercise of the function. It is a qualitativequantitative research with exploratory, descriptive and explanatory purposes, using mixed and structured questionnaire as instrument for data collection. Besides the application of questionnaire, the author used documentary research to collect data through the reading of past auctions records. Research results indicate that, in auctioneers’ opinion, the electronic auction at UFES fulfills in a satisfactory way its objectives, however, it is necessary to improve some decisive points to achieve contest success, such as market price research, elaboration of the Term of Reference, and mainly, the valorization of the auctioneer